O-136 Myeloperoxidase Kit as valuable alternative for LeucoScreen to differentiate round cells in semen samples. (30th June 2022) - Goovaerts, I; Peeters, K; Smet, E; De Neubourg, D
Abstract: Study question: Is Myeloperoxidase Kit, validated for blood but not for semen, a valuable alternative for Leucoscreen to differentiate round cells in semen? Summary answer: Myeloperoxidase Kit is a non-toxic alternative for LeucoScreen to differentiate round cells in semen, with the advantage of assessing a 1:2 dilution of semen. What is known already: As stated in the WHO laboratory manual, the routine assay of peroxidase activity is useful as screening technique for quantifying the leucocyte population in semen samples. The clinically relevant neutrophil leucocytes stain peroxidase positive and can hereby be differentiated from spermatids and spermatocytes. The commercially available kit, Leucoscreen (Fertipro, Beernem, Belgium) uses carcinogenic ortho-toluidine and was therefore withdrawn from the market and an alternative, LeucoScreen Plus, was suggested. A disadvantage of LeucoScreen Plus is the necessity to dilute the sample 1:6. Testing an alternative inexpensive, quick and not carcinogenic method to differentiate round cells without excessive dilutions, is worth investigating. Study design, size, duration: Intra- and inter-variability of Myeloperoxidase Kit (Ral Diagnostics, MLS NV, Menen, Belgium) was assessed by evaluating 2 semen samples 10 times by one technician, and 10 semen samples by 2 technicians, respectively. The stability of the working solution for 5 days was tested on 10 semen samples. The accuracy was tested on 80 samples by comparing Myeloperoxidase Kit with LeucoScreen. The study was performed from July till November 2020. Participants/materials, setting, methods: Working solution was made from the Myeloperoxidase Kit (3/5 bottles): 1 ml alphanaphtol solution, 4 ml pyronine solution and 1 droplet hydrogen peroxide. Semen samples brought to the Andrology Lab for diagnostic evaluation and presenting with round cells were included. To differentiate peroxidase positive leucocytes (dark pink with dark granules) from other round cells (unstained or pink), 10 µl solution was mixed with 10 µl of semen and assessed with phase contrast at 400x. Main results and the role of chance: The intra-variability of round cell differentiation was acceptable with %CV 6.6% for sample 1 (mean ± SD: 30.8% ± 2.04%) and 4.1% for sample 2 (mean ± SD: 56.7% ± 2.31%), both lower than the 10% criterium. The inter-variability was acceptable according to Passing&Bablok (95%CI Intercept A: -1.25 to 0.36; 95%CI Slope B: 0.92 to 1.11) and Spearman rank correlation coefficient (r = 0.983 with P  < 0.001). The stability of the working solution after 5 days, kept at room temperature during the day and at 4 °C at night, compared with freshly made working solution was adequate according to Passing&Bablok (95%CI Intercept A: -2.33 to 0.47; 95%CI Slope B: 0.85 to 1.17) and Spearman rank correlation coefficient (r = 0.991 with P  < 0.0001). Also the accuracy could be accepted as the Bland-Altman plot shows a substantial agreement between Leucoscreen and Myeloperoxidase Kit (difference 0.6%) without a proportional bias. Limitations, reasons for caution: Granules in neutrophils stain differently with Myeloperoxidase Kit, with Leucoscreen and with Leucoscreen Plus, which requires a short adaptation when starting with a new kit. Wider implications of the findings: The use of Myeloperoxidase Kit to differentiate round cells in semen is cheap, non-toxic and easy. It is a valuable asset in the andrology lab because semen samples with low round cell concentrations can be counted in a 1:2 dilution and the working solution can be kept for 5 days. Trial registration number: None